PENGARUH PEMUPUKAN BERIMBANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KENTANG (Solatium tuberosum L.) VARIETAS GRANOLA - Syafri Edi; Endrizal Endrizal (BERITA BIOLOGI, 2011)
Potato is one of the main vegetables in Kerinci District. Development of potato plants is supported by the availability of land, agro ecosystem, labor and market opportunities as well as conductive local government policies. Potato farmers do not fully implementing the recommended farming technologies, such as the use of good seed, balanced fertilizer, crop rotation, pest control, harvesting and post harvest, so the production and reception of farmers is still low. The research took place in Mount Seven Village, Pelompek Kerinci District, Jambi Province which is background by agro-ecosystem dryland upland wet climate (LKDTIB), with soil type andisol at an altitude of 1400 m above sea level. The study aimed to see the effect of balanced fertilization on the growth and yield of potato. Potato used is Granola variety fourth generation derived from the Parent Seed Potato Institute in Kayu Aro. Assessments carried out from February until July 2008, with the treatment as follows: Introduction Package (A): SP-36 450 kg, 200 kg Urea, ZA 200 kg, 300 kg of KC1, NPK 100 kg and 10,000 kg of organic fertilizer/ha. Farmers Package (B): SP-36 750 kg, 400 kg Urea, 250 kg of KC1, and 400 kg NPK /ha. Fanners Package (C): SP-36 600 kg, 300 kg ZA, KC1 300 and 400 kg NPK /ha. The results showed that Package (A) gives the results of 24,320 kg /ha, higher than package (B) with the results of 18,240 kg/ha, while the Fanners Package (C) get the 19,520 kg/ha. High yield Package (A) is supported by the controlled growth of plants, the intensity and the population of pests and diseases and relatively more yield components than Package(B) and Package (C).